Breakdown of HeLa Cell DNA Mediated by Vaccinia Virus - Parkhurst, J. Rodney (1973)
Breakdown of HeLa cell DNA begins within 90 min after infection with vaccinia virus at a multiplicity of infection of 2-plaque-forming units per cell, and ends about 7.5 hr after infection. HeLa cell DNA is degraded to a uniform size of 1 to 2 × 10(7) daltons, as judged by alkaline sucrose sedimentation analysis. The rate of host-cell DNA degradation by vaccinia virus increased directly with the multiplicity of infection. Sedimentation patterns in neutral and alkaline sucrose gradients of viral DNA from infected cells, as well as from partially purified virions, indicated that two size classes of DNA were present. Class 1 DNA sediments like T4 DNA in neutral gradients and has a molecular weight twice that of T4 DNA in alkaline gradients. Class II DNA sediments as a molecule of lower molecular weight than T4 DNA in both types of gradients. Infection of prelabeled HeLa cells with vaccinia virus did not result either in formation of trichloroacetic acid-soluble radioactivity or, upon purification of the virions, radioactivity associated with class I DNA, indicating that vaccinia virus does not reutilize HeLa cell DNA.